The specificity of the organisation of derivative nests Russian emotive verbs and the construction of invariant nested structure - Tretsiakova, Yuliya R. (Journal of the Belarusian State University. Philology, 2022)
The article describes the quantitative-qualitative content of word-formation nests of emotive verbs and also builds a typical nest construction. The study is carried out through descriptive, comparative, component and quantitative analysis of the language material. The individuality of the quantitative and qualitative content of each word-formation nest, which is due to both proper linguistic and extralinguistic factors: the degree of relevance of a potential emotive unit for a native speaker, the presence or absence of metaphor in the semantic field of a potentially producing unit and the presence or absence of more popular lexical analogues. The article describes cases of asymmetry of the word-formation system, including the facts of a discrepancy between word-formation motivation (semantic and structural conditionality of the derivative do not coincide), examples of cross-step formation, penetration of non-usual elements into the structure of the word-formation nest, which is usual in its content (vernaculars, dialectisms, etc.). In connection with the dominance of systematic idea in word-formation, which manifests itself, in particular, in the desire of word-formation units for analogy, the author of the article constructs an invariant word-formation nest that represents extremely typified derivational verticals and horizontals.
Keywords: word-formative nest; invariant word-formative nest; interleaved word-formation; emotive verbs; derivational motivation; word-formative meaning; nomination